Answer: x = 6
Step-by-step explanation: Simplifying
4x + 3x + -7 = 60 + -2x + -13
Reorder the terms:
-7 + 4x + 3x = 60 + -2x + -13
Combine like terms: 4x + 3x = 7x
-7 + 7x = 60 + -2x + -13
Reorder the terms:
-7 + 7x = 60 + -13 + -2x
Combine like terms: 60 + -13 = 47
-7 + 7x = 47 + -2x
Solving
-7 + 7x = 47 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
-7 + 7x + 2x = 47 + -2x + 2x
Combine like terms: 7x + 2x = 9x
-7 + 9x = 47 + -2x + 2x
Combine like terms: -2x + 2x = 0
-7 + 9x = 47 + 0
-7 + 9x = 47
Add '7' to each side of the equation.
-7 + 7 + 9x = 47 + 7
Combine like terms: -7 + 7 = 0
0 + 9x = 47 + 7
9x = 47 + 7
Combine like terms: 47 + 7 = 54
9x = 54
Divide each side by '9'.
x = 6
Simplifying
x = 6